Fabrication and Characterization of a Biomaterial Based on Extracellular-Vesicle Functionalized Graphene Oxide - Driscoll, Julia; Moirangthem, Anuradha; Yan, Irene K.; Patel, Tushar (Frontiers in Bioengineering and Biotechnology, 2021)
Mesenchymal stem cell (MSC) derived extracellular vesicles (EV) are emerging as acellular therapeutics for solid organ injury and as carriers for drug delivery. Graphene-based materials are novel two-dimensional crystal structure-based materials with unique characteristics of stiffness, strength and elasticity that are being explored for various structural and biological applications. We fabricated a biomaterial that would capture desirable properties of both graphene and stem cell derived EV. Metabolically engineered EV that express azide groups were cross-linked with alkyne-functionalized graphene oxide (GO) via a copper catalyzed alkyne−azide cycloaddition (CuAAC) reaction. The crosslinking between EV and GO was accomplished without the need for ligand expression on the metal. Scanning electron and fluorescence microscopy demonstrated excellent cross-linking between EV and GO. Biological effects were assessed by phagocytosis studies and cell viability studies. The uptake of GO or sonicated GO (sGO) resulted in a durable pro-inflammatory immune response. Cell studies further showed that crosslinked GO-EV scaffolds exhibited cell-type dependent cytotoxicity on liver cancer cells whereas there was minimal impact on healthy hepatocyte proliferation. In vitro, neither GO-EV nor sGO-EV induced DNA strand breaks. In vivo studies in zebrafish revealed gross developmental malformations but treatment-induced mortality was only seen with the highest doses of GO-EV and sGO-EV. With these advantages, this engineered biomaterial combining the versatility of graphene with the therapeutic effects of MSC-EV has potential for applications in tissue engineering and regenerative medicine.